2018
DOI: 10.1016/j.molimm.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A1-based cross-reactivity among venoms of clinically relevant Hymenoptera from Neotropical and temperate regions

Abstract: Molecular cross-reactivity caused by allergen homology or cross-reactive carbohydrate determinants (CCDs) is a major challenge for diagnosis and immunotherapy of insect venom allergy. Venom phospholipases A1 (PLA1s) are classical, mostly non-glycosylated wasp and ant allergens that provide diagnostic benefit for differentiation of genuine sensitizations from cross-reactivity. As CCD-free molecules, venom PLA1s are not causative for CCD-based cross-reactivity. Little is known however about the protein-based cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…This approach may be also applied for the identification of Vespula and Polistes venom sensitization. Recently, we showed significant variations in the levels of peptide-based cross-reactivity among PLA1 from Vespinae venoms, even in members of the same genera (Polistinae) [36]. Levels of sIgE against the primary sensitizer were significantly higher.…”
Section: Diagnostic Gapsmentioning
confidence: 94%
See 2 more Smart Citations
“…This approach may be also applied for the identification of Vespula and Polistes venom sensitization. Recently, we showed significant variations in the levels of peptide-based cross-reactivity among PLA1 from Vespinae venoms, even in members of the same genera (Polistinae) [36]. Levels of sIgE against the primary sensitizer were significantly higher.…”
Section: Diagnostic Gapsmentioning
confidence: 94%
“…A recent study showed significant levels of peptide-based cross-reactivity between antigen 5 from several members of Vespinae and Polistinae [27]. Venom PLA1 were shown to cross-react to a lesser extent [10,36].…”
Section: Component-resolved Diagnostics and Peptide Based Cross-reactmentioning
confidence: 98%
See 1 more Smart Citation
“…In Southern Europe, double Vespula-Polistes sensitization is more frequent than Apis-Vespula sensitization [112], and cross-reactivity between allergens of 2 species often poses diagnostic difficulties [113,114]. In cases of difficult interpretation between sensitization Vespula and sensitization to Polistes, the use of Ves v 5 and Pol d 5 seems to be helpful in clinical practice, provided that the difference in specific IgE levels between the 2 molecules is particularly significant, with at least double values of one recombinant over the other [114][115][116].…”
Section: Diagnostic Criteriamentioning
confidence: 99%
“…Although there is a significant number of studies with the venom of P. paulista (Souza et al, 2009;Santo et al, 2011;Pinto et al, 2012;Hoshina et al, 2013;Jacomini et al, 2013;Gomes et al, 2014;Dias et al, 2014Dias et al, , 2015Leite et al, 2015;Vinhote et al, 2017;Perez-Riverol et al, 2018) and some with the venom of E. brunneum (Pluzhnikov et al, 2014;Touchard et al, 2015;Aili et al, 2016) only a few of them investigated intraspecific differences in venom compositions, for example, P. paulista (Mendonça et al, 2017) and E.brunneum Bernardi et al (2017). As the occurrence of these two species is ample, they end up being good study models to evaluate intraspecific differences of their venoms.…”
mentioning
confidence: 99%